2018
DOI: 10.4314/njt.v37i4.36
|View full text |Cite
|
Sign up to set email alerts
|

Study of bacterial associated with kolanut soil plantation and waste looking at their benefits to man and his environment

Abstract: Microorganisms are regarded as the oldest and most abundant life form on earth and their importance to man cannot be over emphasized. They are the occupants and architect of the biosphere maintaining metabolic cycles essential for life. The aim of the study was to explore the benefits and detriments of bacteria associated with kolanut soil plantation and waste to man and the environment. Bacterial was isolated from kolanut soil plantation, decayed, decaying and fresh kolanut waste (testa and husk) obtained fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 37 publications
(42 reference statements)
1
6
0
Order By: Relevance
“…Isolate appeared cream-coloured, regularly shaped, round edges with 1 -2 mm diameter on nutrient agar plate. It was Gram-positive and rod-shaped and conforms to its earlier identification by Fabunmi et al (2018) as L. fusiformis. Organisms showed zones of hydrolysis on xylan agar plates after incubation, indicating its ability to degrade xylan in the media alongside its growth during the incubation period with an average of 29 mm diameter zone of hydrolysis on xylan agar medium.…”
Section: Screening and Authentication Of Obtained Xylanolytic Bacteriasupporting
confidence: 82%
See 1 more Smart Citation
“…Isolate appeared cream-coloured, regularly shaped, round edges with 1 -2 mm diameter on nutrient agar plate. It was Gram-positive and rod-shaped and conforms to its earlier identification by Fabunmi et al (2018) as L. fusiformis. Organisms showed zones of hydrolysis on xylan agar plates after incubation, indicating its ability to degrade xylan in the media alongside its growth during the incubation period with an average of 29 mm diameter zone of hydrolysis on xylan agar medium.…”
Section: Screening and Authentication Of Obtained Xylanolytic Bacteriasupporting
confidence: 82%
“…Gautério et al (2020) and Ratnadewi et al (2020) also buttressed the utility of agriculture waste derivatives like wheat bran, corn cobs, rice straw for exploitation as a lowgrade substrate for xylanase production. Kolanut husk alongside its testa has been proven as a budding substrate to produce the microbial enzyme particularly xylanase (Fabunmi et al 2018). Therefore, the study was carried out to determine the optimal process parameters needed to improve the yield of xylanase produced from simple inexpensive Kolanut husk using Lysinibacillus fusiformis.…”
Section: Introductionmentioning
confidence: 99%
“…The bacterium used in this study was isolated from the soil environment of a kolanut plantation and identified through an extensive biochemical test as well as the molecular gene sequence analysis of its 16S rRNA to ascertain its identity. This microbial species coded strain TB7 in the Laboratory was confirmed to be Lysinibacillus fusiformis and deposited in NCBI database with GenBank accession number MH085463.1 ( Fabunmi et al., 2018 ). The organism was maintained on nutrient agar and sub-cultured periodically all through this study.…”
Section: Methodsmentioning
confidence: 99%
“…Despite this abundance, the wastes remain un-utilized, or at best described as under-utilized. A sizeable number of studies have been carried out on efficient utilization of cocoa [ 47 , 48 , 49 , 50 ] and kolanut [ 50 , 51 , 52 ] wastes. However, while there are some research literature on the employment of cocoa waste for electricity generation, there is paucity of research articles on the use of kolanut waste, or blend of the two, for same purpose.…”
Section: Introductionmentioning
confidence: 99%
“…The model yielded 11.24% and 43.49% of xylose and glucose respectively at high temperature operations; and for low temperature operations, 10.27% and 38.28% respectively. Reviews of literature on the beneficial products accruable from kolanut wastes were presented in [ 51 ] and [ 52 ], wherein production of soap, poultry feeds, microbial enzymes and possibility of biogas were listed as the usefulness. In [ 53 ], kolanut waste was presented as anti-oxidant, while [ 54 ] investigated the anti-microbial activities and potency of the waste, and anti-nutritional composition of same was presented in [ 55 ].…”
Section: Introductionmentioning
confidence: 99%